Perfil do aluno da educação a distância: um estudo no Centro de Referência em Educação a Distância de Pedra Branca do Amapari - Amapá - CARVALHO, Orian Vasconcelos (2024)
Distance learning (DE) has played an important role in the democratization of education, expanding access to formal education for different social groups. This project investigated the profile and factors that influence the learning of students in subsequent technical courses in Environment and Administration, offered through DE by the Pedra Branca do Amapari Reference Center, affiliated with the Porto Grande Agricultural Campus of the Federal Institute of Amapá (IFAP). The overall objective was to identify and analyze the profile and challenges faced by students, considering digital inclusion and the use of virtual learning environments as central factors. The methodology adopted was qualitative, descriptive, and cross-sectional. Data collection was conducted through structured questionnaires administered to freshmen in the aforementioned courses. The research results highlighted technological and pedagogical gaps, such as low familiarity with digital tools, difficulties accessing technological infrastructure, and the need for pedagogical support on the VLE platform. It was found that 39.5% of students had difficulty using digital platforms, highlighting the need for educational interventions. Based on these findings, a teaching proposal called the Mentoreando Mentoring Program was developed and approved. This initiative aims to train students in the effective use of digital tools and the virtual learning environment used by the school. The results showed significant improvements in student engagement, increased autonomy in the virtual learning environment, and greater motivation for retention and success. This study reinforces the importance of investing in digital literacy and pedagogical support as essential tools for social inclusion and reducing school dropout rates in distance learning. The applicability of the Mentoreando program demonstrates that personalized educational strategies can significantly contribute to improving the quality of education in remote and challenging contexts.